2017
DOI: 10.3989/scimar.04493.07a
|View full text |Cite
|
Sign up to set email alerts
|

Habitat preferences among three top predators inhabiting a degraded ecosystem, the Black Sea

Abstract: Summary: This study investigated whether there is evidence of widespread niche partitioning based on environmental factors in the Black Sea and tested the hypothesis that physiographic factors may be employed as predictors. It addresses poorly researched areas with good habitat potential for the only three cetacean subspecies living in this area: the Black Sea short-beaked common dolphin (Delphinus delphis spp. ponticus), the Black Sea bottlenose dolphin (Tursiops truncatus spp. ponticus) and the Black Sea har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The limitation of this method is that, due to the lack of a dedicated sampling, the interpretation of the results should be limited to the differential spatio-temporal use of the study area by the target species when compared with the other species in the same dataset. Specifically, we used a dataset with only presences in a similar way as other studies such as Esteban et al (2013) and Sánchez-Cabanes et al (2017), which provide useful information about the differential distribution of the analyzed cetacean species. This information is valuable when attempting to infer key areas for the life cycle of the species, as is the slope of the Gulf of Lion for fin whales in summer.…”
Section: Discussionmentioning
confidence: 99%
“…The limitation of this method is that, due to the lack of a dedicated sampling, the interpretation of the results should be limited to the differential spatio-temporal use of the study area by the target species when compared with the other species in the same dataset. Specifically, we used a dataset with only presences in a similar way as other studies such as Esteban et al (2013) and Sánchez-Cabanes et al (2017), which provide useful information about the differential distribution of the analyzed cetacean species. This information is valuable when attempting to infer key areas for the life cycle of the species, as is the slope of the Gulf of Lion for fin whales in summer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies by Gladilina and Gol'din (2016) showed that there is a clear difference in group size and distribution density of the bottlenose dolphin among the coastal areas of the Crimean peninsula. Sea depth, surface temperature and salinity can affect the pattern of occurrence and movements of cetaceans (Marini et al 2015, Sanchez-Cabanes et al 2017. The predictive models for the Black Sea cetaceans reveal that depth might be a significant factor that influences their distribution, pointing to a likely association of the common dolphin with greater depths of up to 2250 m, while the bottlenose dolphin and the harbour porpoise prefer the depths of 200-250 m (Sanchez-Cabanes et al 2017).…”
Section: Introductionmentioning
confidence: 96%
“…Sea depth, surface temperature and salinity can affect the pattern of occurrence and movements of cetaceans (Marini et al 2015, Sanchez-Cabanes et al 2017. The predictive models for the Black Sea cetaceans reveal that depth might be a significant factor that influences their distribution, pointing to a likely association of the common dolphin with greater depths of up to 2250 m, while the bottlenose dolphin and the harbour porpoise prefer the depths of 200-250 m (Sanchez-Cabanes et al 2017). Surface temperature is another important predictor of occurrence, with the common dolphin preferring colder waters and the other two species preferring warmer waters (Sanchez-Cabanes et al 2017).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations